The effect of prone positioning on surgical pleth index in patients undergoing spine surgery under general anesthesia - A prospective observational study - Smita Musti; Dhritiman Chakrabarti; Sonia Bansal (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Surgical Pleth Index (SPI) provides an objective assessment of nociception - anti-nociception balance but is influenced by multiple confounders. The effect of change of position on SPI, has not been studied extensively. The aim of the study was to observe the effect of prone positioning on SPI and its correlation with hemodynamic variables, in patients undergoing lumbar and thoracic spine surgery. Material and Methods: This prospective observational pilot study included 14 patients. In addition to hemodynamic monitoring, SPI, entropy and pulse pressure variability (PPV) were monitored. Propofol and Fentanyl infusions were used for maintenance of anesthesia. The patients were made prone on bolsters and all the variables were recorded every 5 minutes in supine position and after making prone for 20 minutes, before and after incision, muscle splitting and laminectomy. Results: Comparing the last value of the variables in the supine position with those immediately after making prone, SPI increased by 16.36 units (P = 0.003), followed by gradual reduction over the next 20 minutes. Mean arterial pressure and heart rate increased transiently (Pvalue = 0.028 and 0.025, respectively) without any significant change in PPV. Surgical incision also led to a significant increase in SPI. Conclusion: Prone positioning leads to significant increase in SPI, probably due to increased sympathetic tone.